Trap-Filling of ZnO Buffer Layer for Improved Efficiencies of Organic Solar Cells - Li, Mingguang; Li, Jing; Yu, Longsheng; Zhang, Ying; Dai, Yizhong; Chen, Runfeng; Huang, Wei (Frontiers in Chemistry, 2020)
Trap-assisted recombination loss in the cathode buffer layers (CBLs) is detrimental to the electron extraction process and severely restricts the power conversion efficiencies (PCEs) of organic solar cells (OSCs). Herein, a novel organic-inorganic hybrid film composed of zinc oxide (ZnO) and 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) is designed to fill the intrinsic charge traps of ZnO-based CBLs by doping F4TCNQ for high-performance inverted OSCs. Thus constructed ZnO:F4TCNQ hybrid film exhibits enhanced surface hydrophobicity and adjustable energy levels, providing favourable interfacial condition for electron extraction process. Consequently, trap-assisted recombination loss in the CBLs was efficiently suppressed, leading to the significantly improved fill factor and PCEs of both fullerene and non-fullerene based OSCs using the ZnO:F4TCNQ hybrid CBLs. This work illustrates a convenient organic acceptor doping approach to suppress the internal charge traps of traditional inorganic CBLs, which will shed new light on the fabrication of high-performance CBLs with facile electron extraction processes in inverted OSC devices.